Thermoanalytical Evidence of Metastable Molecular Defects in Form I of Benzamide - Butterhof, Christian; Martin, Thomas; Ectors, Philipp; Zahn, Dirk; Niemietz, Paul; Senker, Juergen; Nather, Christian; Breu, Josef (Crystal Growth & Design, 2012)
Friedrich Wöhler and Justus von Liebig discovered the first case of molecular polymorphism when crystallizing benzamide in 1832.(1) Thus far only microcrystalline mixtures of metastable phases with the thermodynamically stable form I were available. Optimizing the conditions for crystal growth now gave access to single crystals of the metastable form III which allowed for a detailed comparison of form I and form III by Raman and IR spectroscopy and thermoanalysis. Surprisingly, in the course of detailed differential scanning calorimetry (DSC) measurements for form I an endothermic peak prior to melting was observed. As proven by temperature dependent powder diffraction, thermal microscopy, molecular dynamic (MD) simulations, and solid-state NMR, this premelting thermosignal is not related to an enantiotropic phase transition of form I into form III with a transition temperature close to the melting point. Rather the thermosignal is related to a significant population of metastable defects in form I. While form III melts via a conventional disorder nucleation and growth mechanism, form I accumulates thermally activated metastable point defects involving locally more mobile defect molecules well below Tm. The spin–lattice relaxation experiments suggest an activation barrier larger than 55 kJ/mol. From a combination of DSC, solid state NMR, and MD simulations we provide conclusive evidence for such defects that could play a significant role in selective polymorph transformations of molecular crystals.
EAM Import::2019-03-12